Review tentang Mekanisme Prosedur Kerja Berbagai Sistem Navigasi Satelit - Pratama, Alvin; Situmorang, Amrita Margaretha; Sihombing, Erlina Teresia; Sriyanti , Nora (Jurnal Flight Attendant, 2024)
Satellite navigation has become an integral part of the global infrastructure for a variety of applications, from transportation navigation to earth observation and national security. Satellite navigation systems have become an important part of modern life. This system is used for various purposes, such as vehicle navigation, asset tracking, and communication. Each system has different working mechanisms and procedures. This research aims to identify the working procedures of various satellite navigation systems in the world. The research method used is a qualitative descriptive method through literature study sourced from journals, scientific articles, books and other relevant sources. The results of this research show that satellite navigation systems, such as GPS, use radio signals to determine location on the earth's surface. GPS consists of three main parts, namely control, space, and user. GPS satellites send signals that are used to determine position, speed, direction, and time. GPS has wide-ranging uses, including in ship navigation, object tracking, and management of agricultural to military supply chains.